Desenvolvimento de biossensor amperométrico baseado em monoamina oxidase-b para detecção de neurotransmissores - Pereira, Tamyris Paschoal (Universidade Federal de São Carlos, 2015)
This work focuses on the production of nanostructured films of poly (ethyleneimine) PEI together with MAO-b free and encapsulated in liposomes constructed by the layer-bylayer technique (LbL), for application in biosensors. Liposomes are microscopic vesicles composed of concentric lipid bilayers separated by aqueous medium, capable of encapsulating hydrophilic and/or hydrophobic molecules, which are, respectively, included in the aqueous compartment and the membrane or adsorbed. Enzymes encapsulated in liposomes have advantages in stability and catalytic activity compared to the free enzyme. Liposomes were synthesized by using a rotary evaporator and subsequently the enzyme was immobilized. The phospholipids dipalmitoyl phosphatidyl glycerol (DPPG) and palmitoyl oleoyl phosphatidyl glycerol (POPG) and the mixture of the two were used in this study in the ratio (1:1) and (1:4) (m/m). To build a biosensor in neurotransmitter monoamine oxidase b on, thin films were set up on poly (ethyleneimine) PEI together with monoamine oxidase b enzyme (MAO-B) immobilized or not in liposomes and deposited on ITO electrodes, being the Prussian blue a mediator of electrons. The obtained films were characterized by fluorescence spectroscopy, UV-visible and circular dichroism. The results indicated that the film is deposited successfully on quartz and ITO. The amperometric measurements were performed to detect the film sensitivity and the detection limits and check which architecture is best suited for the best composition of the biosensor. The results achieved until now show that the liposome retain the conformational structure of the enzyme and films composed of PEI / MAO-B + POPG:DPPG in proportion (1:4) (w/w) indicate better performance of the biosensor, due to the sensitivity value of 0.33 ± 0.02 µA.cm-2 mM-1 found and a good selectivity.
Keywords: Biossensores; Biosensors; Neurotransmissores; Neurotransmitters; Materiais nanoestruturados; Nanostructured materials; Dopamina; Lipossomos; Filmes nanoestruturados; Dopamine; Nanostructured films; Liposomes; OUTROS